Development of Flipbooks Based on Guided Inquiry Models to Train Science Process Skills of Junior High School Students on Temperature and Heat Materials - Masna Awaliyah; Wahono Widodo; Eko Haryono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This development aims to produce a flipbook-based guided inquiry learning model to train science process skills that are feasible in terms of validity, practicality, and effectiveness. Method: The type of research used is development research. The development model used is the 4D model (define, design, develop, and disseminate). The assessment instrument used in this study consisted of learning device validation sheets and science process skills tests. Results: Based on the results of data analysis, it can be concluded that digital-based flipbooks obtain an average validation in the valid category. These results indicate that flipbooks can be used as learning media. Novelty: The novelty of this research is an inquiry-based feature on flipbooks about temperature and heat, which can train students' science process skills. In addition, the developed inquiry-based Flipbook is also a digital flipbook.